Pengaruh Penggunaan Biaya Hidup KIP – Kuliah dan Tingkat Literasi Keuangan Terhadap Pemenuhan Kebutuhan Mahasiswa Pendidikan Ekonomi - Yulia Nor Frassiska; Sugeng Pradikto (Jurnal Manajemen Riset Inovasi, 2025)
The purpose of this study was to analyze the effect of the use of KIP-Kuliah costs and financial literacy levels on student needs. The study was conducted on 45 KIP-Kuliah recipient students at Universitas PGRI Wiranegara. Data collection was carried out using a questionnaire designed to test the variables of KIP-Kuliah living costs, financial literacy, and student needs. The data were then analyzed using multiple linear regression methods. Based on the results of the study, the level of financial literacy has a positive and significant effect on student needs, with a coefficient of determination of approximately 0.596 (p <0.05). In contrast, the use of KIP-Kuliah living costs does not have a significant effect on student needs (p>0.05). Overall, these variables have an average contribution of 39.9% to the student needs variable. This shows that financial literacy is an important component in maximizing the use of knowledge by students to meet their master's needs. Based on the research findings, steps that can be taken include increasing literacy through education or training programs and evaluating the KIP-Kuliah program to ensure that the funds are used effectively.